Enthalpy of dissolution and thermal dehydration of calcium oxalate hydrates - Sádovská Galina; Wolf Gert (Springer, 2015)
The enthalpies of dissolution of calcium oxalate hydrates at 25 A degrees C were calculated from indirect calorimetric experiments requiring three easy measurable reactions. The first reaction was dissolution of calcium oxalate hydrates in hydrochloric acid, dissolution of sodium oxalate in hydrochloric acid was used as the second, and dissolution of sodium oxalate in tetramethylammonium chloride as the last one. The results Delta(diss) H = 21.1, 20.8 and 31.7 kJ mol(-1) correspond to mono-, di- and trihydrate form. Dehydration enthalpy of these hydrates was determined by DSC method in the temperature range of 20-300 A degrees C. Corresponding values of Delta(deh) H for dehydration of 1, 2 and 3 mol of water from calcium oxalates are 66.5, 83.6 and 143.9 kJ mol(-1). The estimation of enthalpy of formation from DSC experiments gives values -1,984 and -2,296 kJ mol(-1) for calcium oxalate dihydrate and trihydrate, respectively. The enthalpy contribution of the water in the calcium oxalate hydrates calculated from the determined values of the dehydration and dissolution enthalpy using two different calorimetric methods is compared.
Rozpouštěcí entalpie a dehydratace hydrátů šťavelanu vápenatého
Keywords: Calcium oxalate hydrates; Calorimetry; Enthalpy; Dehydration; Dissolution; Formation; hydtráty šťavelanu vápenatého; kalorimetrie; entalpie; dehydratace; rozpouštění; vznik